2013
DOI: 10.4028/www.scientific.net/amr.832.724
|View full text |Cite
|
Sign up to set email alerts
|

Different Surface Morphology of Annealed PVDF-TrFE Thin Films and the Effect on its Ferroelectric Properties

Abstract: The different morphology of 250 nm PVDF-TrFE (70:30 mol%) thin films were observed in relation to its ferroelectricity. The annealing temperatures were varied from solvent evaporation (Ts), Curies transition (Tc), up to melting temperature (Tm). It was found that the annealing process promoted the development of elongated crystallite structure also known as ferroelectric crystal, which significantly improved the ferroelectric properties of PVDF-TrFE (70:30 mol%) thin films. However, the presence of nanoscale s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Similar observations were made previously by several other workers . The transformation of smooth surface morphology into fiber‐like rough morphology with increasing annealing temperature has been attributed to the fusion of neighboring grains into rods, resulting in the formation of long extended fiber‐shaped crystals . It was observed that length of these rods increases with increasing annealing temperatures .…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Similar observations were made previously by several other workers . The transformation of smooth surface morphology into fiber‐like rough morphology with increasing annealing temperature has been attributed to the fusion of neighboring grains into rods, resulting in the formation of long extended fiber‐shaped crystals . It was observed that length of these rods increases with increasing annealing temperatures .…”
Section: Resultssupporting
confidence: 87%
“…Further, presence of defects such as HH, TT, or ‐TrFE content in the crystalline regions of P(VDF‐TrFE) as also evidenced from Figure (c) causes a reduction in orientation of polymer chains. These defects being detrimental to the ferroelectric properties of P(VDF‐TrFE) films can cause reduction in the values of P r and also increment in coercive field values . From SEM micrographs of Figure (d–f), it can be seen that P(VDF‐TrFE) rich melt‐mixed blends consist of needle and fiber‐like structures.…”
Section: Resultsmentioning
confidence: 96%